تحليل المزيج الترويجي في مؤسسة خدمية - راضية, العروم; صفاء, دو (جامعة الوادي - University of Eloued, 2023)
من خلال هذه الدراسة يمكن القول انه لكي تضمن المؤسسة نجاحها واستمرارها على أكمل وجه، لابد عليها ان تبني وتطور مزيجها الترويجي وبفعل هذا التطور تتمكن من الوصول الى اذهان المستهلكين المحددين فتحفزهم على اتباعها والحصول على منتجاتها وخدماتها، كل هذا يأتي من خلال الاهتمام المستمر بالمستهلك والتعرف على حاجاته ورغباته للتعرف على ماذا يريد المستهلك وتلبية تلك الحاجات والرغبات. Through this study, it can be said that in order for the organization to ensure its success and continuity to the fullest, it must build and develop its promotional mix, and by doing this development it can reach the minds of specific consumers, motivating them to follow it and obtain its products and services, all this comes through continuous interest in the consumer and identification on his needs and desires to identify what the consumer wants and meet those needs and desires.
Keywords: المزيج الترويجي، المستهلك، الحاجات ،الرغبات; Promotional mix Consumer Needs Desires